Anchoring Amongst the Waves: Discursive Constructions of Motherhood and Addiction - Kilty, Jennifer M.; Dej, Erin (Qualitative Sociology Review, 2012)
The authors problematize essentialized notions of motherhood both ideologically and through criminalized women’s accounts of correctional programming discourses that engage these notions as a way to foster “motherhood as praxis.” Using data from interviews conducted with former female prisoners, we analyze how substance using mothers invoke the concept of a “good” mother by negotiating its meaning through techniques of self-surveillance and the surveillance of other criminalized mothers. Women use this renegotiated identity as inspiration to move away from activities in conflict with motherhood, such as using drugs and/or alcohol. Correctional authorities in drug rehabilitation programs encourage women to use motherhood as an “anchor” upon which to stop using and the women appeal to this identity to responsibilize their actions. Dichotomizing conceptualizations of a selfless, nurturing, and chaste mother with an addict identity is in fact a precarious rehabilitation tactic. We hypothesize that women who feel they cannot live up to the idealized notion of motherhood might use drugs to cope with feelings of inadequacy, a point that requires further research. Using a framework where motherhood is the key to recovery not only reinforces the addict identity should a woman relapse, it necessarily indicates failure as a mother.